KUSHONLAR DAVLATI TARIXSHUNOSLIGIDA SHOKIR PIDAYEV ASRLARINING AHAMIYATI - Mahmarahimova Hilola, Meyliyev Alpjamol (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
The article provides information about the role of Shakir Pidayev in the history of the Kushan state. In addition, the ancient city of Termiz during the Kushan dynasty was also described.